Empowering Mother Language Special reference:Critical edition of ancient text ‘Sarala Mahabharata’ - Bijayalaxmi Dash (IJRDO- Journal of Educational Research, 2020)
This paper aims at Pioneering the level of mother languages in Odisha and the language rank, identicalness of language, language transpose and language restoration through the endorsement of mother language in school and higher education. In this context society has gamboled an integral role regarding the modernization and maintenance of modern language in education and literary field also. Embracing the modern language by the state has established a cultural, constructive civilizing democracy. In this field we faced various primary challenges due to shortfall of govt. plan, shortage of academic institution and lack of mother language teacher from primary to University level. A swing of writing and revitalizing mother language through generating literature, cataloguing literary organizations, publishing literary magazines, journals and periodicals digitization and critical edition of classic literature are some of the examples that directly empower our mother language. This paper aims at Pioneering the level of mother languages in Odisha and the language rank, identicalness of language, language transpose and language restoration through the endorsement of mother language in school and higher education. In this context society has gamboled an integral role regarding the modernization and maintenance of modern language in education and literary field also. Embracing the modern language by the state has established a cultural, constructive civilizing democracy. In this field we faced various primary challenges due to shortfall of govt. plan, shortage of academic institution and lack of mother language teacher from primary to University level. A swing of writing and revitalizing mother language through generating literature, cataloguing literary organizations, publishing literary magazines, journals and periodicals digitization and critical edition of classic literature are some of the examples that directly empower our mother language.